Pengaruh Financial Stability Perusahaan dan Ineffective Monitoring terhadap Keefektivitasan Pengawasan Fraudulent Financial Reporting - Indah Rizqi Permatasari; Lina Reviliana Lova Audina; Mazel Hartanto; Dien Noviany Rahmatika (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to provide a comprehensive understanding of the influence of financial stability and ineffective monitoring on fraudulent financial reporting. Employing a Systematic Literature Review (SLR) method, this study examines 55 national journal articles published between 2021 and 2025, evaluated based on methodological accuracy, relevance, and their contribution to the topic of fraudulent financial reporting. The results identify several influencing factors, notably financial stability, which appeared 18 times, and ineffective monitoring, which appeared 15 times in the reviewed literature. The analysis concludes that financial stability consistently influences the occurrence of reporting fraud; when a company's financial condition is threatened by economic or industrial factors, management is prone to manipulating financial statements to conceal poor performance. Meanwhile, ineffective monitoring provides opportunities for management to commit fraud, particularly regarding the supervisory function when the board or audit committee does not operate substantively.